An Experimental Study on Strength Characteristics and Hydration Mechanism of Cemented Ultra-Fine Tailings Backfill - Deqing, Gan; Hongbao, Li; Chao, Chen; Hongjian, Lu; Youzhi, Zhang (Frontiers in Materials, 2021)
In order to study the strength characteristics and hydration mechanism of the cemented ultra-fine tailings backfill (CUTB), the uniaxial compressive strength (UCS) tests of CUTB and cemented classified tailings backfill (CCTB) with cement-tailing ratio (C/T ratio) of 1:4 and 1:6 and curing ages of 3, 7, 14 and 28 days were carried out. The hydration products and morphology of the cemented paste backfill (CPB) were analyzed by X-ray diffraction (XRD) and scanning electron microscope (SEM). The results show that the UCS of the CUTB is significant compared to the CCTB under the same conditions; the greater the C/T ratio and curing age, the greater the UCS difference value. The UCS growth curve of the CUTB is approximately S-shaped, and there is a relationship between the UCS and curing age. The ultra-fine tailings particles in the CUTB have potential activity; in the alkaline environment–generated cement hydration, active SiO2 and Al2O3 particles undergo secondary hydration reaction, resulting in no or very little Ca (OH)2 crystals generated in the CUTB, and the hydration products and morphology are also different.